THE EFFECT OF ESTAFET WRITING TECHNIQUE ON WRITING RECOUNT TEXT AT GRADE X STUDENTS OF SMA SWASTA HARAPAN PADANGSIDIMPUAN - Siregar, Desy Ilmedianti (CV. Alfa Pustaka, 2024)
This research aimed to know the effect of using Estafet Writing Technique on writing Recount Text at grade X Students of SMA Swasta Harapan Padangsidimpuan. In this research, the researcher used one-group pretest-posttest design, there was not control group. The researcher gave pre-test to student, then, researcher gave the students’ treatment about writing Recount Text with Estafet Writing Technique. After treatment is given, researcher gives the student post-test. The population in this research were the students of SMA Swasta Harapan Padangsidimpuan. The researcher used purposive sampling were takes class of X IPA 1 as the sample of this research. The total of students in this class was 23 students. The score of students' before using Estafet Writing Technique was 56.04 and it was categorized